TIGIT enhances CD4+ regulatory T‐cell response and mediates immune suppression in a murine ovarian cancer model - Chen, Fengzhen; Xu, Yanying; Chen, Yulong; Shan, Shu (Cancer medicine (Malden, MA), 2020)
Ovarian cancer (OC) is the fifth‐leading cause of cancer‐related death in women with a pathogenesis involving activation of regulatory T cells (Tregs). The T‐cell immunoglobulin and ITIM domain (TIGIT) is a well‐known immune checkpoint molecule that inhibits T‐cell responses. However, the role of TIGIT in OC is not comprehensively understood. In this study, we revealed crucial functions of TIGIT in the development and progression of OC. ID8 cells were used to establish a murine OC model. TIGIT expression was increased in immune cells of OC mice, particularly in CD4+ Tregs. Anti‐TIGIT monoclonal antibodies (mAb) were used to block the function of TIGIT in OC mice, and we found that the anti‐TIGIT treatment reduced the proportion of CD4+ Tregs, but did not affect CD4+ and CD8+ T cells or natural killer cells. Splenic CD4+ Tregs from OC mice were isolated after the anti‐TIGIT treatment, and their functioning was examined. Inhibition of TIGIT lowered the degree of immunosuppression induced by CD4+ Tregs. A survival curve suggested that anti‐TIGIT treatment can improve the survival rate of OC in mice. We conclude that TIGIT enhanced CD4+ Tregs response and mediated immunosuppression in the OC model. Our data suggest that inhibition of TIGIT is a potential therapeutic target in OC patients. TIGIT enhanced CD4+ Tregs response and mediated immune suppression in OC; TIGIT is a potential target in OC patients.